(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between physical fitness and the personal development of elementary school students. The method used was quantitative correlation with a sample of students in grades IV, V, and VI from several elementary schools. Physical fitness data was measured using the Indonesian Physical Freshness Test (TKJI), while personal development was measured through questionnaires. The results of the analysis showed that there was a significant positive relationship between physical fitness and personal development, with a Spearman correlation coefficient of 0.185 (p = 0.009). Although the relationship is weak, these findings indicate that physical fitness contributes to students’ personal development, which includes aspects of self-confidence, responsibility, and social skills. This study suggests that schools and parents pay more attention to the importance of physical activity in supporting children’s personal development.